2022
DOI: 10.1186/s12879-022-07843-z
|View full text |Cite
|
Sign up to set email alerts
|

Why do men who have sex with men practice condomless sex? A systematic review and meta-synthesis

Abstract: Background Despite a large amount of behavioral interventions to reduce human immunodeficiency virus (HIV)-related high-risk sexual behaviors, consistent condom use remains suboptimal among men who have sex with men (MSM). However, current databases are lack of synthesized evidence to explain why MSM practiced condomless sex. Objective Our study aims to conduct a systematic review and meta-synthesis of 39 eligible qualitative studies to explore the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 74 publications
0
13
0
1
Order By: Relevance
“…The respondents had an average attitude towards the prevention of Mpox (54%); general practices towards prevention were also average (41%) with most persons (58.2%) having a poor response to prevention practices. Evidence from Shen et al [25] revealed the existence of individual barriers such as lack of HIV/STIrelated knowledge and substance use; interpersonal-level barriers where safe sex was an indication of distrust; and structural-level barriers that may include power imbalance in the sexual relationship; as reasons for unsafe sexual practices among MSM. These can be extrapolated to the attitude and prevention practices found among the community in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The respondents had an average attitude towards the prevention of Mpox (54%); general practices towards prevention were also average (41%) with most persons (58.2%) having a poor response to prevention practices. Evidence from Shen et al [25] revealed the existence of individual barriers such as lack of HIV/STIrelated knowledge and substance use; interpersonal-level barriers where safe sex was an indication of distrust; and structural-level barriers that may include power imbalance in the sexual relationship; as reasons for unsafe sexual practices among MSM. These can be extrapolated to the attitude and prevention practices found among the community in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The second reason most cited was the aversion to using a condom, more frequently cited among people with a low educational level. A recent systematic review revealed that the MSM population believes that not using condoms represents mutual trust and loyalty between sexual partners, while condom use is a symbol of distrust or suspicion regarding the partner's HIV status (33).…”
Section: Discussionmentioning
confidence: 99%
“…117–172). Since the first step was performed in our previous study [ 44 , 45 ], this study describes the following steps to develop the CRSS.…”
Section: Methodsmentioning
confidence: 99%
“…We used the qualitative data from our previous meta-synthesis [ 44 ] to generate an item pool with 87 items. Then, our team brainstormed to reduce the item pool to 53 items.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation